Dinamika dan Perubahan Sosial Pendidikan Islam Sebagai Agent Perubahan - Sumarno Sumarno; Radjiman Ismail; H. Moh. Natsir Mahmud (Peneliti.net, 2023)
Social change can occur all the time, meaning that social change will continue to occur at any time, because in essence humans are God's creatures who are dynamic, that is, they will continue to experience change, as we know, previously only able to find out the latest news from newspapers, now we can find out the latest news via the internet. - Social changes that occur are planned, and also often occur unplanned, meaning that here social change can occur either planned by the humans themselves or will even occur outside the plans of the humans themselves, such as family planning programs and natural disasters. Social change will definitely bring positive and negative impacts. The positive impacts that result from social change are the advancement of technology in various people's lives and the complexity of various tools and equipment to meet life's needs, while the negative impacts resulting from social change are the fading of values and norms in society, and people's lives becoming consumptive or excessive. .